KOMPARASI OPTIMALISASI PERALATAN MEKANIS PADA KEGIATAN PENGUPASAN OVERBURDEN MENGGUNAKAN METODE KAPASITAS PRODUKSI DAN METODE OVERALL EQUIPMENT EFFECTIVENESS (OEE) - Hisni Rahmi; Afni Nelvi (Sekolah Tinggi Teknologi Industri Padang, 2022)
The company's production target in overburden stripping is 200 BCM/hour, while the actual in the field is still below the production target. Therefore, it is necessary to optimize production using queuing theory. Queuing theory is a method that can be used to calculate and model the behavior of trucks and loaders in open pits so that loading activities take place better. The purpose of this research is to optimize the productivity of digging and loading equipment using queuing theory. The primary data needed is the loading and unloading cycle time, transportation equipment cycle time, repair time, standby time, working time. Secondary data needed in the form of available working time by the company. The results of the study resulted in the actual productivity of the excavator is 140.59 BCM/hour with the production capacity method and 106.68 BCM/hour using the OEE method, while the dumptruck is 135.33 BCM / hour with the production capacity method and 161.78 BCM/hour using the OEE method where it has not met the production target. Productivity after being optimized for excavator loading and unloading equipment increased by 52.74% to 297.49 BCM / hour using the production capacity method and increased by 58.85% to 259.24 BCM / hour using the OEE method, while dumptruck productivity increased by 36.85% to 214.31 BCM / hour with the production capacity method and increased by 22.47% to 208.68 BCM / hour using the OEE method which has met the production target.